(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
Ferro- geopolymer is Recent trending building material which replace cement for construction. Geopolymer mortar as a matrix and wire mesh as a reinforcement together called as ferro- geopolymer. Geopolymer is a by-product material such as Fly ash, Rice husk ash, GGBS, Blast furnace slag etc., which are rich in silicon and aluminum. Use of geopolymer mortar reduce the pollution due to release of CO2 into the air. Ferrocement is simply a cement mortar reinforced by a steel wire meshes of different shapes. Aim of this project is to Investigation of using geopolymer mortar in ferrocement by varying the combination, number and sizes of meshes. In this paper we are going to use geopolymer mortar, GGBS material is used with sodium silicate and sodium hydroxide. Ferrocement that means wire meshes such as Square woven, Square welded and Expanded metal mesh is used. The number of layers in each mesh was varied from single, double and triple layers. Mortar Mix of 1:3 have to take. Optimum molarity has to find out and then casting of cubes for 150mm *150 mm* 150 mm have to done, to check the desire w/c ration as well as molarity. Specimen have to cure for 28 days with ambient curing. Further casting of slab specimen of 1100mm * 400mm * 150mm have to cast with ferro geopolymer by varying the combination, number and sizes of meshes. Flexural behavior, acid attack, corrosion resistance test and long-term other test etc. preformation provision is done and effectiveness of the Square woven, Square welded and Expanded metal mesh were compared. Total nine rectangular slab have to cast with different meshes such as square woven, square welded and expanded metal mesh.